'200 years of white affirmative action': White privilege discourse in discussions of racial inequality. (March 2014) - Hastie, Brianne; Rimmington, David
Since the seminal work of McIntosh, research on multiple forms of privilege (race, gender, sexuality, (dis)ability, class, religion) has expanded, with a particular focus on how inducing recognition of privilege can build support for equality. However, evidence has been mixed on whether interventions increase support for policies designed to redress inequality. The present study looks at how respondents use arguments about privilege in naturalistic discussions, in this case, 357 online comments regarding a US Supreme Court ruling of racial discrimination. In particular, we can see how four cumulative strategies build to allow the presentation of racial privilege: connecting past to current inequality; constructing ongoing unequal treatment as contributing to current disadvantage; reclaiming 'liberal' arguments for 'liberal' ends; and defining group differences as consisting of both disadvantage and privilege. These strategies can be deployed to build a privilege discourse to contest inequality and racism. This provides potential strategies for privilege-based interventions to achieve their aims in increasing support for equality policies.